2017
DOI: 10.1002/ece3.3163
|View full text |Cite
|
Sign up to set email alerts
|

Genome size in arthropods; different roles of phylogeny, habitat and life history in insects and crustaceans

Abstract: Despite the major role of genome size for physiology, ecology, and evolution, there is still mixed evidence with regard to proximate and ultimate drivers. The main causes of large genome size are proliferation of noncoding elements and/or duplication events. The relative role and interplay between these proximate causes and the evolutionary patterns shaped by phylogeny, life history traits or environment are largely unknown for the arthropods. Genome size shows a tremendous variability in this group, and it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 50 publications
(64 reference statements)
3
69
0
Order By: Relevance
“…After controlling for both spatial autocorrelation and potential phylogenetic patterns, we found a marginally significant, positive correlation between ant genome size similarity and climate similarity (Mantel R = 0.14, p-value = 0.055). Although genome size similarity and MASH genome similarity were not significantly correlated (Mantel R = 0.08, p-value = 0.217), we included MASH as a covariate in addition to geodesic distance because previous research indicated that genome size is associated with phylogenetic relatedness (Alfsnes et al, 2017). We found that different spatial and climatic variables were associated with the size similarity of ant genomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After controlling for both spatial autocorrelation and potential phylogenetic patterns, we found a marginally significant, positive correlation between ant genome size similarity and climate similarity (Mantel R = 0.14, p-value = 0.055). Although genome size similarity and MASH genome similarity were not significantly correlated (Mantel R = 0.08, p-value = 0.217), we included MASH as a covariate in addition to geodesic distance because previous research indicated that genome size is associated with phylogenetic relatedness (Alfsnes et al, 2017). We found that different spatial and climatic variables were associated with the size similarity of ant genomes.…”
Section: Resultsmentioning
confidence: 99%
“…We are cautious to offer possible mechanisms for this trend. In the general context of arthropods, genome size appears to be influenced by a complex array of selection pressures, as evidenced by the recent study by Alfsnes et al (2017), which found that genome size patterns varied greatly among major arthropod taxa with high potential for different mechanisms affecting genome size. For example, insects displayed clear phylogenetic correlations with genome size while genome size patterns in crustaceans were nearly independent of phylogeny but strongly related to biogeographic gradients (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, genome size has been associated with specific habitats and environmental conditions. Marine crustaceans are likely to have larger genomes than freshwater and terrestrial ones (Jeffery 2015;Alfsnes et al 2017); within the marine realm, polar species tend to have larger genomes compared to temperate species (Hessen and Persson 2009;Jeffery 2015;Leinaas et al 2016). Jeffery (Jeffery 2015) hypothesizes that such large genomes may result from the expansion of transposable elements and other repetitive elements, due to relaxed selection for rapid development or reduced constraints on body size in predictable and stable marine polar environments, compared to more fluctuating environments.…”
Section: Genomic Resources For Marine Zooplanktonmentioning
confidence: 99%
“…Nevertheless, evidence from insects and crustaceans suggest that accumulation of transposable and repetitive elements may be the primary contributor to their large genome sizes (Alfsnes et al 2017), while polyploidization is probably not the most common driver of genome evolution in zooplankton (Gregory and Hebert 1999). For example, species of the copepod genera Calanus and Pseudocalanus exhibit quantum shifts in genome size (C-values) within each genus, but share similar chromosome complements (McLaren et al 1989).…”
Section: Genomic Resources For Marine Zooplanktonmentioning
confidence: 99%